Effect of sodium bicarbonate on performance and markers of kidney and gastrointestinal injury during repeated sprints in the heat - Jonathan W. Specht; Marissa Ramirez; Jennifer Raef; Mackenzie Schwartz; Alyssa R. Bailly; Oscar Chavez; Ozan Kumbasar; Jade X. Dawson; Jessica Apodaca; Raul Freire; Whitley C. Atkins; Flávio de Castro Magalhães; et al. (European Journal of Applied Physiology, 2026)
Purpose We tested the hypotheses that sodium bicarbonate (SB) supplementation improves performance, reduces markers of acute kidney injury (AKI) risk, and increases markers of acute gastrointestinal injury (AGI) during repeated sprints in the heat. Methods Using a double-blind design, 10 recreationally endurance-trained participants ingested 0.2 g/kg of body weight of SB or placebo before cycling in the heat (dry-bulb: 40 °C, relative humidity: 20%). Exercise bouts included a 22-min warm-up, then 4-sets of 5 × 6-sec maximal-effort standing cycling sprints. Core temperature (Tc) was measured at baseline, end of warm-up, after set two of sprints, and post-exercise bouts. Urine and plasma collected pre-ingestion and pre-, post-, and 1-h post-exercise were analyzed for markers of AKI risk, AGI, and endotoxemia. Results SB increased peak (average difference between conditions: 21 ± 11 W, condition effect: p = 0.02) and average ( p = 0.03) power across the sprints. Tc increased from pre- to post-exercise (placebo: Δ1.3 ± 0.3 °C, SB: Δ1.4 ± 0.4 °C, time effect: p < 0.001), but there were no effects of condition or interaction. Exercise increased the primary marker of AKI (urinary IGFBP7×TIMP-2, time effect: p = 0.005) but not urinary NGAL. There were no condition or interaction effects for either AKI marker. Plasma I-FABP, a marker of AGI, increased post-exercise bouts (placebo: Δ291 ± 550 pg/mL, SB: Δ397 ± 482 pg/mL, p = 0.03), with no condition or interaction effects. There were no significant effects for markers of endotoxemia (LBP, sCD14). Conclusions SB supplementation improves repeat sprint performance in the heat without altering Tc, markers of AKI risk, or markers of AGI.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Effects of an intervention for a liquefied petroleum gas cook-stove with free fuel on food insecurity and dietary diversity among women and infants: a multi-country randomized controlled trial - Sheela S. Sinharoy; Rina Das; Anaité Diaz-Artiga; Lisa M. Thompson; Ghislaine Rosa; John McCracken; Miles A. Kirby; Carla Tarazona-Meza; Vigneswari Aravindalochanan; Shirin Jabbarzadeh; Jiantong Wang; Ajay Pillarisetti; et al. (Food Security, 2026)

Household air pollution and blood pressure among adult women participants of the Household Air Pollution Intervention Network Trial: An exposure-response analysis - Ajay Pillarisetti; Wenlu Ye; Jennifer L. Peel; Howard Chang; Lindsay J. Underhill; Kalpana Balakrishnan; Anaité Díaz-Artiga; John P. McCracken; Ghislaine Rosa; Lisa M. Thompson; Vigneswari Aravindalochanan; Dana Boyd Barr; et al. (Environmental Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Evaluation of ploidy and the DNA index by flow cytometry in central nervous system tumors: a review - Fernandez-Sanchez David; Ramirez-Corona Juan Antonio; Perez-Becerra Jose de Jesus; Santana-Bejarano Uriel Francisco; Santana-Hernandez Jennifer; Corona-Rivera Alfredo; Rodriguez-Machuca Victor Ulises; Bobadilla-Morales Lucina (Molecular Biology Reports, 2024)

Myocardial infarction during treatment of Crotalinae envenomation: A case report - Jacob Robishaw-Denton; Jennifer Ramirez; Alisia Bahadir; Geoffrey Smelski (Toxicon, 2024)

Simulation of blind pre-diction and post-diction shaking table tests on a masonry building aggregate using a continuum modelling approach - Abide Aşıkoğlu; Jennifer D’Anna; Rafael Ramirez; Fabio Solarino; Antonio Romanazzi; Maria Pia Ciocci; Nicoletta Bianchini (Bulletin of Earthquake Engineering, 2024)
Masonry buildings of historical centres are usually organized within aggregates, whose structural performance against seismic actions is challenging to predict and constitutes still an open issue. The SERA—AIMS (Seismic Testing of Adjacent Interacting Masonry Structures) project was developed to provide additional experimental data by testing a half-scale, two-unit stone masonry aggregate subjected to two horizontal components of dynamic excitation. In this context, this paper investigates the reliability of the modelling approach and the assumptions adopted to generate a three-dimensional continuum finite element model. The work involves two stages, namely a blind pre-diction and a post-diction phase, and proposes a series of simulation analyses including a strategy to shorten the actual records and save computation costs. The study was performed to investigate the extent of uncertainty in modelling for such masonry aggregates in relation to the experimental outcomes. Pre-diction results were proven to be not accurate in terms of predicted displacements and damage patterns. The upgrades introduced for the post-diction analyses, including the calibration of the elastic modulus and the introduction of a non-linear interface between the two units, allowed to improve the outcomes, with reasonable results in terms of predicted base shear force, displacements along Y-direction and damage pattern for the non-linear stage. The overall approach showed to be appropriate for the structural analysis of existing masonry aggregates, but the accurate modelling of this type of structure remains challenging due to the high level of uncertainties.

Accelerating ocean species discovery and laying the foundations for the future of marine biodiversity research and monitoring - Alex David Rogers; Hannah Appiah-Madson; Jeff A. Ardron; Nicholas J. Bax; Punyasloke Bhadury; Angelika Brandt; Pier-Luigi Buttigieg; Olivier De Clerck; Claudia Delgado; Daniel L. Distel; Adrian Glover; Judith Gobin; et al. (Frontiers in Marine Science, 2023)
Ocean Census is a new Large-Scale Strategic Science Mission aimed at accelerating the discovery and description of marine species. This mission addresses the knowledge gap of the diversity and distribution of marine life whereby of an estimated 1 million to 2 million species of marine life between 75% to 90% remain undescribed to date. Without improved knowledge of marine biodiversity, tackling the decline and eventual extinction of many marine species will not be possible. The marine biota has evolved over 4 billion years and includes many branches of the tree of life that do not exist on land or in freshwater. Understanding what is in the ocean and where it lives is fundamental science, which is required to understand how the ocean works, the direct and indirect benefits it provides to society and how human impacts can be reduced and managed to ensure marine ecosystems remain healthy. We describe a strategy to accelerate the rate of ocean species discovery by: 1) employing consistent standards for digitisation of species data to broaden access to biodiversity knowledge and enabling cybertaxonomy; 2) establishing new working practices and adopting advanced technologies to accelerate taxonomy; 3) building the capacity of stakeholders to undertake taxonomic and biodiversity research and capacity development, especially targeted at low- and middle-income countries (LMICs) so they can better assess and manage life in their waters and contribute to global biodiversity knowledge; and 4) increasing observational coverage on dedicated expeditions. Ocean Census, is conceived as a global open network of scientists anchored by Biodiversity Centres in developed countries and LMICs. Through a collaborative approach, including co-production of science with LMICs, and by working with funding partners, Ocean Census will focus and grow current efforts to discover ocean life globally, and permanently transform our ability to document, describe and safeguard marine species.

Addressing SNAP Education Training and Program Implementation Needs Within a Land Grant University System - Brenda Derrick; Nicki Griffin; Julie Moreschi; Vanessa Ramirez-Prado; Trinity Allison; Jennifer McCaffrey (Journal of Nutrition Education and Behavior, 2023)

Effect of cover cropping on soil organic matter characteristics: Insights from a five-year field experiment in Nebraska - Christopher O. Anuo; Jennifer A. Cooper; Katja Koehler-Cole; Salvador Ramirez; Michael Kaiser (Agriculture, Ecosystems & Environment, 2023)

Improving cervical cancer screening rates: a scoping review of resources and interventions - Madyson L. Popalis; Sarah I. Ramirez; Kelsey M. Leach; Marni E. Granzow; Kelsey C. Stoltzfus; Jennifer L. Moss (Cancer Causes & Control, 2022)

Bushfire smoke plume composition and toxicological assessment from the 2019–2020 Australian Black Summer - Jack B. Simmons; Clare Paton-Walsh; Asher P. Mouat; Jennifer Kaiser; Ruhi S. Humphries; Melita Keywood; David W. T. Griffith; Adhitya Sutresna; Travis Naylor; Jhonathan Ramirez-Gamboa (Air Quality, Atmosphere & Health, 2022)
Many of the population centres in southeast Australia were swathed in bushfire smoke during the 2019–2020 austral summer. Bushfires burning during what is now known as the Black Summer was historically large and severe, and the fire season historically long. The chemical composition in the gas and aerosol phase of aged plumes measured near Wollongong, NSW in early 2020 is reported in this work. Enhancement ratios to carbon monoxide are presented for thirteen species (acetaldehyde, acetone, acetonitrile, black carbon aerosol, benzene, methane, methacrolein + methyl vinyl ketone, methyl ethyl ketone, methanol, ammonium ion PM 1 fraction, nitrate ion PM 1 fraction, organic PM 1 fraction and PM 2.5 ). Observed plume composition is comparable to that measured in fresh smoke from Australian fires reported in the literature. Enhancements of biogenic volatile organic compounds such as isoprene (smoke-effected period mean 1 ppb, maximum 6 ppb) were observed along with elevated concentrations of particulate variables. Enhancement ratios reported here can be used in plume modelling of landscape-scale fires and assist in concentration estimates of infrequently measured atmospheric pollutants. The relative toxicological contribution of species present in the plumes was determined for plume exposure at the measurement site and for concentrated plumes at a population centre case study. Similar results were apparent at both locations. Contributions to the toxicological loading were dominated by respirable particles (~ 52–63% total contribution), formaldehyde (~ 30–39% total contribution) and acrolein. This is a reminder to consider the toxicological contributions in the gas phase when considering health impacts of population exposure to bushfire smoke.

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Differential effects of aging on spatial abilities - Daniela E. Aguilar Ramirez; Jarrod Blinch; Kate Takeda; Jennifer L. Copeland; Claudia L. R. Gonzalez (Experimental Brain Research, 2022)

Genomic Analysis of two NDM-1 Providencia stuartii Strains Recovered from a Single Patient - Amparo Hoard; Sabrina Montaña; Alessandro Moriano; Jennifer S. Fernandez; German M. Traglia; Cecilia Quiroga; Agustina Franchi; Emilia Cohen; Cecilia Corigliano; Marisa Almuzara; Maria Soledad Ramirez (Current Microbiology, 2020)

Determinants of vulnerability of bean growing households to climate variability in Colombia - Lisset Perez; David A. Rios; Diana C. Giraldo; Jennifer Twyman; Genowefa Blundo-Canto; Steven D. Prager; Julian Ramirez-Villegas (Climate and Development, 2020)

Effect of Host Human Products on Natural Transformation in Acinetobacter baumannii - Brettni Quinn; German M. Traglia; Meaghan Nguyen; Jasmine Martinez; Christine Liu; Jennifer S. Fernandez; Maria Soledad Ramirez (Current Microbiology, 2019)

A Study on Acinetobacter baumannii and Staphylococcus aureus Strains Recovered from the Same Infection Site of a Diabetic Patient - Nancy Castellanos; Jun Nakanouchi; Dennis Irfan Yüzen; Sammie Fung; Jennifer S. Fernandez; Claudia Barberis; Lorena Tuchscherr; Maria Soledad Ramirez (Current Microbiology, 2019)

Whole Genome Sequence Analysis of Burkholderia contaminans FFH2055 Strain Reveals the Presence of Putative β-Lactamases - José J. Degrossi; Cindy Merino; Adela M. Isasmendi; Lorena M. Ibarra; Chelsea Collins; Nicolás E. Bo; Mariana Papalia; Jennifer S. Fernandez; Claudia M. Hernandez; Krisztina M. Papp-Wallace; Robert A. Bonomo; Miryam S. Vazquez; et al. (Current Microbiology, 2019)

Whole mitochondrial genomes illuminate ancient intercontinental dispersals of grey wolves ( Canis lupus ) - Stephan Koblmüller; Carles Vilà; Belen Lorente‐Galdos; Marc Dabad; Oscar Ramirez; Tomas Marques‐Bonet; Robert K. Wayne; Jennifer A. Leonard (Journal of Biogeography, 2016)
Aim Grey wolves ( Canis lupus ) are widespread across the Holarctic. Here, we test the previously proposed hypothesis that extant North American wolves originate from multiple waves of colonization from Asia. We also test the hypothesis that land connections have been important in the evolutionary history of other isolated wolf populations in Japan. Location Holarctic. Methods We analyse 105 previously published and newly obtained complete mitochondrial genomes from a geographically diverse sample of grey wolves and date critical branches in the phylogenetic tree. Phylogeographical hypotheses are tested in an approximate Bayesian computation approach. Results We find that the mitogenomes of all living wolves in North America, including Mexican wolves, most likely derive from a single colonization event from Eurasia that expanded the grey wolf range into North America. This colonization occurred while a land bridge connected Eurasia and North America before the Cordillerian and Laurentide ice sheets fused in the Last Glacial Maximum, c . 23 ka, much more recent than predicted based on the fossil record. Pleistocene land bridges also facilitated the separate colonization of Hokkaido and the southern Japanese islands. Main conclusions Extant wolf lineages in North America derive from wolves that migrated into North America coincident with the formation of the most recent land bridge with Eurasia. The maternal lineages from earlier Pleistocene American wolves are not represented in living American wolves, indicating that they left no descendants. The timing of colonization of North America, Hokkaido and the southern Japanese islands corresponds to the changes in land connectivity as a consequence of changing sea level.

Improving Environmental and Social Targeting through Adaptive Management in Mexico's Payments for Hydrological Services Program - KATHARINE R. E. SIMS; JENNIFER M. ALIX‐GARCIA; ELIZABETH SHAPIRO‐GARZA; LEAH R. FINE; VOLKER C. RADELOFF; GLEN ARONSON; SELENE CASTILLO; CARLOS RAMIREZ‐REYES; PATRICIA YAÑEZ‐PAGANS (Conservation Biology, 2014)
Natural resource managers are often expected to achieve both environmental protection and economic development even when there are fundamental trade‐offs between these goals. Adaptive management provides a theoretical structure for program administrators to balance social priorities in the presence of trade‐offs and to improve conservation targeting. We used the case of Mexico's federal Payments for Hydrological Services program (PSAH) to illustrate the importance of adaptive management for improving program targeting. We documented adaptive elements of PSAH and corresponding changes in program eligibility and selection criteria. To evaluate whether these changes resulted in enrollment of lands of high environmental and social priority, we compared the environmental and social characteristics of the areas enrolled in the program with the characteristics of all forested areas in Mexico, all areas eligible for the program, and all areas submitted for application to the program. The program successfully enrolled areas of both high ecological and social priority, and over time, adaptive changes in the program's criteria for eligibility and selection led to increased enrollment of land scoring high on both dimensions. Three factors facilitated adaptive management in Mexico and are likely to be generally important for conservation managers: a supportive political environment, including financial backing and encouragement to experiment from the federal government; availability of relatively good social and environmental data; and active participation in the review process by stakeholders and outside evaluators. Mejorando los Objetivos Ambiental y Social Mediante el Manejo Adaptativo en el Programa de Pagos por Servicios Hidrológicos en México

Modelling-based assessment of suspended sediment dynamics in a hypertidal estuarine channel - Laurent O. Amoudry; Rafael Ramirez-Mendoza; Alejandro J. Souza; Jennifer M. Brown (Ocean Dynamics, 2014)

Rapid conversion of EUCOMM/KOMP-CSD alleles in mouse embryos using a cell-permeable Cre recombinase - Edward Ryder; Brendan Doe; Diane Gleeson; Richard Houghton; Priya Dalvi; Evelyn Grau; Bishoy Habib; Evelina Miklejewska; Stuart Newman; Debarati Sethi; Caroline Sinclair; Sapna Vyas; et al. (Transgenic Research, 2014)

Cancer Stage Knowledge and Desire for Information: Mismatch in Latino Cancer Patients? - Rosario Costas-Muniz; Rohini Sen; Jennifer Leng; Abraham Aragones; Julia Ramirez; Francesca Gany (Journal of Cancer Education, 2013)

Molecular Characterization of Mutant Mouse Strains Generated from the EUCOMM/KOMP-CSD ES Cell Resource - Edward Ryder; Diane Gleeson; Debarati Sethi; Sapna Vyas; Evelina Miklejewska; Priya Dalvi; Bishoy Habib; Ross Cook; Matthew Hardy; Kalpesh Jhaveri; Joanna Bottomley; Hannah Wardle-Jones; et al. (Mammalian Genome, 2013)

Predictors of regional establishment success and spread of introduced non‐indigenous vertebrates - Craig R. Allen; Kristine T. Nemec; Donald A. Wardwell; Justin D. Hoffman; Mathew Brust; Karie L. Decker; Daniel Fogell; Jennifer Hogue; Aaron Lotz; Thaddeus Miller; Marcy Pummill; Luis E. Ramirez‐Yañez; et al. (Global Ecology and Biogeography, 2013)
Aim To provide the first analysis of predictors of both establishment and spread, both within and across taxa, for all vertebrate taxa within a region. We used F lorida, USA , as our study system because it has a well‐documented history of introduction and invasion, and is a hotspot for biological invasions. Location F lorida, USA. Methods We analysed non‐indigenous species ( NIS ) data from peninsular F lorida – which included both successful and unsuccessful introductions from all vertebrate classes – to determine the best predictors of both establishment and spread for fish (65 species), herpetofauna (63 species), birds (71 species) and mammals (25 species). We used 10 variables proposed to be associated with the establishment and spread of NIS : body mass, geographic origin, reproductive rate, diet generalism, native‐range size, latitude of native range, number of NIS present at date of introduction, presence of NIS congeners, morphological proximity to other NIS (in terms of body mass) and propagule pressure. A multimodel selection process was used with an information‐theoretic approach to determine the best fit models for predicting establishment and spread of NIS . We selected a priori plausible predictive models for establishment and spread. Results Large native‐range size and small body mass best predicted establishment of non‐indigenous herpetofauna. The presence of NIS congeners had the largest positive effect on the establishment of non‐indigenous fish. For mammals, the number of NIS present at the time of introduction best explained establishment. No single model best explained bird establishment. For all taxa but birds, the number of NIS present at time of introduction was included in at least one of the best‐supported models for explaining spread. Main conclusions Our analyses suggest that predictors of establishment and spread differ across vertebrate taxa at the scale studied. Most predictive variables can be interpreted as measures of competitive interactions among species.

“Doctor, What Do I have?” Knowledge of Cancer Diagnosis Among Immigrant/Migrant Minorities - Francesca Gany; Lalanthica Yogendran; Dana Massie; Julia Ramirez; Trevor Lee; Gary Winkel; Lisa Diamond; Jennifer Leng (Journal of Cancer Education, 2013)

Evidence of negative impacts of ecological tourism on turtlegrass (Thalassia testudinum) beds in a marine protected area of the Mexican Caribbean - Jorge A. Herrera-Silveira; Just Cebrian; Jennifer Hauxwell; Javier Ramirez-Ramirez; Peter Ralph (Aquatic Ecology, 2010)

The Effects of l-theanine on Alpha-Band Oscillatory Brain Activity During a Visuo-Spatial Attention Task - Manuel Gomez-Ramirez; Simon P. Kelly; Jennifer L. Montesi; John J. Foxe (Brain Topography, 2009)

The Arabidopsis CLV3-like (CLE) genes are expressed in diverse tissues and encode secreted proteins - Vijay K. Sharma; Julio Ramirez; Jennifer C. Fletcher (Plant Molecular Biology, 2003)